The Chumatski Songs as a Repertoire of Future Artists Theoretical and Instrumental Training: Array - Bukhnieva, Olena; Bankul, Larysa; Wang, Chen (Journal of Danubian Studies and Research, 2021)
The article considers a large layer of Ukrainian song folklore – chumatski songs, which have a prominent place in the system of Ukrainian social lyrics. It is determined that chumatski songs are an essential part of the spiritual culture of the Ukrainian people. These songs reproduce the conceptual positions of representatives of trade and coaching and should be the subject of synthetic interdisciplinary research, including theoretical and instrumental training of future artists. The article emphasizes the role of chumatstvo in the processes of nation-building related to the formation of the sphere of Ukrainian national aesthetics and worldview. The relevance of the study is determined by the need to understand chumatski songs as signs of ethnoculture of the Ukrainian people, the ways of its existence and spiritual revival.